Marginal land conversion to perennial energy crops with biomass removal enhances soil carbon sequestration. Issue 10 (8th August 2022) - Xu, Yi; Zhou, Jie; Feng, Wenhao; Jia, Rong; Liu, Chunyan; Fu, Tongchen; Xue, Shuai; Yi, Zili; Guillaume, Thomas; Yang, Yadong; Peixoto, Leanne; Zeng, Zhaohai; et al.
Abstract: Marginal land conversion to perennial energy crops can provide biomass feedstocks and climate change mitigation. However, the effect of perennial energy crop cultivation on soil organic carbon (SOC) sequestration and its underlying mechanism in marginal land still remains incomplete. Here, SOC turnover, stability, and its potential sequestration were evaluated based on 10 years of land use change from C3 grass‐dominated marginal land to C4 energy crops Miscanthus and switchgrass cultivation. The naturally occurring 13 C signature down to 60 cm depth was used to determine the energy crops‐derived C. Compared to reference marginal land, Miscanthus plantation increased the SOC stock at 0–60 cm depth by 17.8% and 64.3% in bulk and root zone, respectively. Similarly, the SOC stock under switchgrass was also 16.5% and 93.0% higher in bulk and root zone than in reference marginal land, respectively. The higher SOC stock in the root zone of switchgrass relative to Miscanthus was supported by the higher contribution of C4 ‐derived C to SOC (44.5% vs. 32.4%). The mean residence time of old C was higher under switchgrass than Miscanthus in the bulk zone across 0–60 cm ( p < 0.05) but remained the same at 0–20 cm in the root zone. Specific SOC mineralization and temperature sensitivity were lower in soils under Miscanthus and switchgrass compared to reference marginal land. The partial least squares path model revealed that perennial energy crop cultivation enhances soil C stock via increased C4 ‐derived C input and reduced mineralization. In conclusion, marginal land conversion to perennial energy crops is a win–win strategy for C sequestration to mitigate climate change and support the growing bioenergy sector with biomass supply. Abstract : Marginal land conversion to perennial energy crops increased soil C stocks. Switchgrass had a higher soil C sequestration potential than Miscanthus . New C4 ‐C input exceeds old C3 ‐C losses via mineralization leading to C sequestration.